First Person Squared A Study of Co-Authoring in the Academy - Day, Kami (University Press of Colorado, 2001)
In (First Person)2, Day and Eodice offer one of the few book-length studies of co-authoring in academic fields since Lunsford and Ede published theirs over a decade ago. The central research here involves in-depth interviews with ten successful academic collaborators from a range of disciplines and settings. The interviews explore the narratives of these informants' experience-what brought them to collaborate, what cognitive and logistical processes were involved as they worked together, what is the status of collaborated work in their field, and so on-and situate these informants within the broader discussion of collaboration theory and research as it has been articulated over the last ten years. As the study develops, Day and Eodice become most interested in the affective domain of co-authorship, and they find the most promising explorations of that domain in the work of feminist theorists in composition. Against a background of feminist theory, the reflections of these informants and authors not only provide a window into the processes of current scholarship in writing, but also come to stand as a critique of traditional practice in English departments. Throughout the book, the two co-authors interrupt themselves with reflections of their own, on the rejection long ago of their proposal to co-author a dissertation, on their presuppositions about their research, on their developing commitment to the framework of feminist theory to account for their findings, and on their own processes and challenges in writing this book. The result is a well-centered volume that is disciplined and restrained in its presentation of research, but which is layered and multivocal in presentation, and which ends with some provocative conclusions.